2018
DOI: 10.1155/2018/7809535
|View full text |Cite
|
Sign up to set email alerts
|

Refractory Abdominal Pain in a Patient with Chronic Lymphocytic Leukemia: Be Wary of Acquired Angioedema due to C1 Esterase Inhibitor Deficiency

Abstract: Acquired angioedema due to C1 inhibitor deficiency (C1INH-AAE) is a rare and potentially fatal syndrome of bradykinin-mediated angioedema characterized by episodes of angioedema without urticaria. It typically manifests with nonpitting edema of the skin and edema in the gastrointestinal (GI) tract mucosa or upper airway. Edema of the upper airway and tongue may lead to life-threatening asphyxiation. C1INH-AAE is typically under-diagnosed because of its rarity and its propensity to mimic more common abdominal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…Regarding the type of the underlying disease, we assessed similar incidence rates to the data found in the literature. 32% of our patients were diagnosed with a lymphoproliferative disorder, while the literature mentions 27–64% [ 1 , 8 , 9 , 15 , 26 ]. MGUS was found in 53% of our patients, while other studies reported 32–48% [ 4 , 10 , 15 , 26 ].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Regarding the type of the underlying disease, we assessed similar incidence rates to the data found in the literature. 32% of our patients were diagnosed with a lymphoproliferative disorder, while the literature mentions 27–64% [ 1 , 8 , 9 , 15 , 26 ]. MGUS was found in 53% of our patients, while other studies reported 32–48% [ 4 , 10 , 15 , 26 ].…”
Section: Discussionmentioning
confidence: 94%
“…32% of our patients were diagnosed with a lymphoproliferative disorder, while the literature mentions 27–64% [ 1 , 8 , 9 , 15 , 26 ]. MGUS was found in 53% of our patients, while other studies reported 32–48% [ 4 , 10 , 15 , 26 ]. Besides following-up the C1–INH-AAE of our patients, they are regularly monitored for the underlying disease as well.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…2,[6][7][8][9][10][11] Angioedema can occur in all body regions and can lead to a life-threatening state; if the edema occurs in the larynx, it can lead to suffocation. 1,4,6,9,[12][13][14][15] Several factors can have a role in the development of the symptoms; widely used angiotensin converting enzyme inhibitor (ACEIs) antihypertensives must be highlighted, 9,12,16 but estrogen containing oral contraceptives, 4,9,17 mechanical trauma, psychological stress, bacterial or viral infections may also contribute to the development of edematous attacks. 1,4,8 C1-INH-AAE often accompanies malignant diseases, usually lymphomas, monoclonal gammopathy of undetermined significance (MGUS) or autoimmune diseases that contribute to the development of the angioedema with the following: 2, 6, 8, 9, 13, 16, 18-20 1) the increased activation of the classic complement pathway causes an increased usage of the C1-INH protein, which causes a relative shortage.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic lymphocytic leukemia, a B-cell lymphoproliferative disorder, is characterized by the progressive accumulation of functionally incompetent lymphocytes, and its diagnosis may pose challenges due to variable and often benign clinical presentations [ 2 ]. The link between CLL and AAE highlights the importance of recognizing this association, as AAE may be associated with CLL, necessitating comprehensive evaluation and management strategies [ 3 ].…”
Section: Introductionmentioning
confidence: 99%